2000
DOI: 10.1111/j.1939-1676.2000.tb02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine Methyltransferase in Red Blood Cells of Dogs, Cats, and Horses

Abstract: Our objective was to determine if thiopurine methyltransferase (TPMT), the enzyme important in the metabolism of azathioprine in human beings, is detectable in red blood cell lysates (RBCL) of healthy dogs, cats, and horses. Values for TPMT activity were determined from blood collected from 20 healthy dogs, cats, and horses. The TPMT activity in each animal's RBCL was determined using a radioenzymatic end point involving TPMT-facilitated metabolism of 6-mercaptopurine to 6-methylmercaptopurine (6-MMP). One uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Two previous studies that included a much smaller number of cats also reported that levels of RBC TPMT activity in this species were only approximately one-fifth of those observed in humans or dogs (Foster et al, 2000;White et al, 2000). If RBC TPMT activity reflects the level of this enzyme activity in other cat tissues, these relatively low levels of activity may help to explain the sensitivity of this species to thiopurine therapy (Beale et al, 1992).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Two previous studies that included a much smaller number of cats also reported that levels of RBC TPMT activity in this species were only approximately one-fifth of those observed in humans or dogs (Foster et al, 2000;White et al, 2000). If RBC TPMT activity reflects the level of this enzyme activity in other cat tissues, these relatively low levels of activity may help to explain the sensitivity of this species to thiopurine therapy (Beale et al, 1992).…”
Section: Discussionmentioning
confidence: 88%
“…The thiopurine drugs that are metabolized by TPMT are also used to treat companion animals, including cats, and companion animals also display large individual variations in thiopurine efficacy and toxicity (Houston and Taylor, 1991;Rinkhardt and Kruth, 1996). Cats in particular have been reported to be especially sensitive to myelosuppression after azathioprine therapy (Beale et al, 1992), and some authors have even recommended that these drugs not be used to treat cats (White et al, 2000). If principles of individualized therapy based, in part, on pharmacogenetics are of value when applied to humans, it is reasonable to ask whether similar principles might also apply to companion animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drugs were slowly tapered and discontinued, and the horse has not relapsed. In humans and rodents azathioprine is metabolized in the liver (and possibly other organs) by thiopurine methyltransferase (TPMT) an enzyme detectable in human lysed red blood cells (RBC) 36,37 . When the TPMT RBC enzyme level was measured in dogs, cats and horses, it was found that the level was highest in dogs, lower in cats and lowest in horses 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of azathioprine in cats is reportedly associated with a life-threatening leukopenia and thrombocytopenia (Beale 1990, Beale et al 1992, Plumb 1999, Scott et al 2001, that could be attributed to the low erythrocyte thiopurine methyltransferase activity in this animal species (Foster et al 2000, Papich 2000, White et al 2000. Lower doses of azathioprine, such as 0.3 mg/kg BW, once daily (Papich 2000), 0.3-0.5 mg/kg BW every 48 hours (Birchard and Sherding 2000) or 1.5-3.125 mg/cat every 48 hours (Papich 1995), are thought to be relatively safer.…”
Section: Discussionmentioning
confidence: 99%